Social Policy Review 21 : Analysis and debate in social policy, 2009 - Holden, Christopher; Greener, Ian; Rummery, Kirstein (Book collections on Project MUSE., 2009)
'Social Policy Review' provides students, academics and all those interested in welfare issues with critical anayyses of progress and change in areas of major interest during the past year.